Acalabrutinib Versus Ibrutinib in Previously Treated Chronic Lymphocytic Leukemia: Results of the First Randomized Phase III Trial. Issue 31 (1st November 2021) - Byrd, John C.; Hillmen, Peter; Ghia, Paolo; Kater, Arnon P.; Chanan-Khan, Asher; Furman, Richard R.; O'Brien, Susan; Yenerel, Mustafa Nuri; Illés, Arpad; Kay, Neil; Garcia-Marco, Jose A.; Mato, Anthony; et al.
Abstract : PURPOSE: Among Bruton's tyrosine kinase inhibitors, acalabrutinib has greater selectivity than ibrutinib, which we hypothesized would improve continuous therapy tolerability. We conducted an open-label, randomized, noninferiority, phase III trial comparing acalabrutinib and ibrutinib in patients with chronic lymphocytic leukemia (CLL). METHODS: Patients with previously treated CLL with centrally confirmed del(17)(p13.1) or del(11)(q22.3) were randomly assigned to oral acalabrutinib 100 mg twice daily or ibrutinib 420 mg once daily until progression or unacceptable toxicity. The primary end point was independent review committee–assessed noninferiority of progression-free survival (PFS). RESULTS: Overall, 533 patients (acalabrutinib, n = 268; ibrutinib, n = 265) were randomly assigned. At the data cutoff, 124 (46.3%) acalabrutinib patients and 109 (41.1%) ibrutinib patients remained on treatment. After a median follow-up of 40.9 months, acalabrutinib was determined to be noninferior to ibrutinib with a median PFS of 38.4 months in both arms (95% CI acalabrutinib, 33.0 to 38.6 and ibrutinib, 33.0 to 41.6; hazard ratio: 1.00; 95% CI, 0.79 to 1.27). All-grade atrial fibrillation/atrial flutter incidence was significantly lower with acalabrutinib versus ibrutinib (9.4% v 16.0%; P = .02); among other selected secondary end points, grade 3 or higher infections (30.8% v 30.0%) and Richter transformations (3.8% v 4.9%) were comparable between groups and median overall survival was not reached in either arm (hazard ratio, 0.82; 95% CI, 0.59 to 1.15), with 63 (23.5%) deaths with acalabrutinib and 73 (27.5%) with ibrutinib. Treatment discontinuations because of adverse events occurred in 14.7% of acalabrutinib-treated patients and 21.3% of ibrutinib-treated patients. CONCLUSION: In this first direct comparison of less versus more selective Bruton's tyrosine kinase inhibitors in CLL, acalabrutinib demonstrated noninferior PFS with fewer cardiovascular adverse events.